Identification and Validation of Reference Genes for Quantitative Gene Expression Analysis in Ophraella communa - Zhang, Yan; Chen, Jiqiang; Chen, Guangmei; Ma, Chao; Chen, Hongsong; Gao, Xuyuan; Tian, Zhenqi; Cui, Shaowei; Tian, Zhenya; Guo, Jianying; Wan, Fanghao; Zhou, Zhongshi (Frontiers in Physiology, 2020)
Quantitative real-time PCR (qPCR) is one of the most common technologies for evaluating the expression level of target genes. Suitable reference genes are essential to ensure the accuracy of the qPCR results. Ophraella communa is an effective bio-control agent of the invasive common weed. By now, the reference genes in O. communa have not yet been screened and validated. The aim of this study was to screen for the most stable reference genes under in different background, such as different developmental stages, sexes, tissues, and in males with different body sizes.We selected 12 common housekeeping genes involved in different biological processes including GAPDH, ACT1, ACT2, ARF1, ARF4, SDH, βTUBC, RPL4, RPL19, RPS18, EF1α, COX as the candidate reference genes. To analyze the stability of the candidate reference genes we first used three dedicated algorithms, GeNorm, NormFinder, and BestKeeper, and further comprehensive ranking was provided by ReFinder. The results showed that RPL19 and RPL4 exhibited the least variation in different developmental stages/sexes and in males of different body sizes. COX proved to be most suitable for normalizing gene expression levels in different tissues, and coincidentally, RPL19 was also found to be second in terms of stability in this study. To the best of our knowledge, this is the first study to identify suitable reference genes for analyzing gene expression in O. communa, thus, this study would lay the foundation for future research in the molecular physiology and biochemistry of O. communa and other insects.